FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA BERKARIR SEBAGAI AKUNTAN PUBLIK(Studi Empiris pada Mahasiswa Program Studi S1 Akuntansi Fakultas Ekonomi dan Bisnis Universitas Lambung Mangkurat) - Pramisty, Thata Surya; Rizani, Fahmi (SINERGI : Jurnal Riset Ilmiah, 2025)
The purpose of this study is to examine and analyze the financial benefits that are offered, professional training, professional recognition, work environment, work-related stress, interpersonal relationships, and community dynamics in relation to Bachelor of S1 Akuntansi Faculty of Economics and Business at Universitas Lambung Mangkurat. The study's sample consisted of 797 active students from the S1 Academic Program at Universitas Lambung Mangkurat. There are around 286 respondents to this survey. The sample preparation method is nonprobability sampling using purposive sampling technique. The type of data that is used is called primer data. The data collection technique used in this study is called kuesionering. Multiple regression analysis, handled by the SPSS 26 program, is the data analysis method used in this study. The study concludes that the interest of Bachelor of Accounting students at Lambung Mangkurat University's Faculty of Economics and Business is significantly influenced by factors related to the job market and family environment. In the meantime, the interests of Lambung Mangkurat University's Bachelor of Accounting students are not significantly impacted by monetary awards, professional training, professional recognition, work environment, or personality